1988
DOI: 10.1002/smi.2460040403
|View full text |Cite
|
Sign up to set email alerts
|

Do anxiety patients with or without frequent panic attacks differ in their respnse to stress?

Abstract: To evaluate different responses in norepinephrine (NE), epinephrine (E), heart rate (HR), electrodermal activity (EDA) and subjective ratings to a 'neutral' and a 'patient-specific' stressor we compared nine anxiety patients with three or more panic attacks during the past week, 10 patients with no panic attacks during the past week and 10 controls, at baseline as well as during two stressors: a videotape containing horror scenes and a tape showing a patient having a panic attack. Both patient groups exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…However, it is not clear what differences in situations and/or patients led to some reports of normal levels and other reports of elevations; perhaps surprisingly, plasma catecholandne and MHPG levels do not appear to be significantly increased during unexpected (Cameron et al 1987b), lactate-induced (Liebowitz et al 1985;Carr et al 1986), or caffeiae-iMuced (Chamey et al 1985) anxiety and panic attacks. It is possible that patients are more reactive to stressful circumstances than are normal subjects, and that adret~ergically mediated physiological variables show excessive increases in anxious patients in those circumstances, but are normal under minimally stressful situations such as those in the present study (Albus et al 1987(Albus et al , 1988; see also Cameron and Nesse 1988).…”
Section: Discussionmentioning
confidence: 71%
“…However, it is not clear what differences in situations and/or patients led to some reports of normal levels and other reports of elevations; perhaps surprisingly, plasma catecholandne and MHPG levels do not appear to be significantly increased during unexpected (Cameron et al 1987b), lactate-induced (Liebowitz et al 1985;Carr et al 1986), or caffeiae-iMuced (Chamey et al 1985) anxiety and panic attacks. It is possible that patients are more reactive to stressful circumstances than are normal subjects, and that adret~ergically mediated physiological variables show excessive increases in anxious patients in those circumstances, but are normal under minimally stressful situations such as those in the present study (Albus et al 1987(Albus et al , 1988; see also Cameron and Nesse 1988).…”
Section: Discussionmentioning
confidence: 71%
“…Research suggests that the normal HR and skin conductance response to a potentially threatening situation is initially characterized by a decrease (e.g., HR shows deceleration) followed by an increase depending on the actual threat value (i.e., intense threat does produce an increase in autonomic arousal as part of the fight-or-flight response; see Barlow, 2002). However, research has shown that adults with anxiety disorders are more likely than controls to have elevated baseline arousal and display a more pronounced response (e.g., heart rate remains elevated after the stimulus is removed) to stressors (Albus, Braune, Hoehn, & Scheibe, 1988;Cole, Zahn-Waxler, Fox, Usher, & Welsh, 1996;Harrison & Turpin, 2003;Lee & Olness, 1996;Tremayne & Barry, 1990;Zahn, Nurnberger, Berrettini, & Robinson, 1991).…”
Section: Department Of Psychology University Of New Orleansmentioning
confidence: 97%
“…In response to a potentially threatening and stress-evoking situation, normal heart rate response is characterized by an initial decrease followed by an increase depending upon the perceived threat value of the situation (Barlow, 2002). However, research has shown that individuals with anxiety disorders compared to controls have elevated baseline heart rate arousal and display a more pronounced and sustained response to stressors (Albus, Braune, Hö hn, & Scheibe, 1988;Cole, Zahn-Waxler, Fox, Usher, & Welsh, 1996;Harrison & Turpin, 2003;Lee & Olness, 1996;Zahn, Nurnberger, Berrettini, & Robinson, 1991).…”
mentioning
confidence: 96%